The use of plant extracts to control tilapia reproduction: Current status and future perspectives. Issue 3 (28th October 2021) - Abaho, Ivan; Masembe, Charles; Akoll, Peter; Jones, Clifford L. W.
Abstract: Control of prolific reproduction is vital for a profitable tilapia aquaculture enterprise. All‐male tilapia culture is a popular method used to control prolific breeding, because the male individuals grow faster than female and mixed‐sex populations. Presently, most farmers use 17α‐methyl testosterone (MT) to produce all‐male tilapia individuals, although synthetic hormones are linked to human health and environmental risks. Recently, considerable attention has focused on plant‐based products as alternatives to MT, because they are affordable, safe, and eco‐friendly. Despite the growing interest in using plant extracts to prevent frequent spawning in tilapia production, the available information is not collated to standardize application guidelines. Accordingly, this review article consolidates existing knowledge on the use of plant extracts to control prolific breeding in tilapia culture systems. In addition, limitations to commercial application of the extracts are identified. To date, seed, root, and leaf extracts of 20 plant species, most notably, Tribulus terrestris, Mucuna pruriens, and Carica papaya, exhibit potential for controlling unwanted breeding in tilapia production systems. The extracts are mainly administered orally, incorporated in fish feeds. Saponins and flavanoids are the main bioactive compounds in the phytoextracts, which induce sex inversion and fertility impairment in tilapia. The commercialization of plant extracts is, however, hampered by lack of standardized information on extract preparation, optimal dosages, and mechanism of action. Thus, future studies should address these technical limitations and highlight economic incentives for commercial use of plant extracts in tilapia aquaculture.